Finding a New Normal: Maternal Experiences Transitioning to Home From the Neonatal Intensive Care Unit Caring for Technology-Dependent Infants. (February 2022) - Norton, Michelle; Hagstrom, Amy
Abstract : Background: Infants discharged from the neonatal intensive care unit (NICU) dependent on medical technology (eg, respiratory or nutritional support) are a growing vulnerable population. These infants are medically fragile, prone to emergency department visits and readmissions, and require increased caregiver demands at home. The experiences of their maternal caregiver's after NICU discharge however, are not well understood. Purpose: This qualitative descriptive study addressed this knowledge gap by interviewing mothers of technology-dependent infants about their experience during their first 2 weeks transitioning to home from the NICU. This is a critical period in which mothers must first assume advanced caretaking responsibilities in the home. Methods: Eight mothers participated in semistructured audio-recorded interviews via the Web conferencing system Zoom and completed demographic questionnaires. Results: Five themes emerged from the data that described essential features of the mothers' transition to home: ( a ) needing coordinated discharge care; ( b ) establishing a routine; ( c ) being an advocate; ( d ) having a support system; and ( e ) finding normalcy. An additional important finding of this study was the presence of maternal posttraumatic stress and postpartum depression. Implications for Practice: Results highlight the importance of providing mothers hands-on practice opportunities and identifying social support and home healthcare options prior to discharge of technology-dependent infants. Implications for Research: Future research should focus on multidisciplinary interventions targeted toward discharge preparation, transitional support, and understanding maternal psychiatric symptoms among mothers of technology-dependent infants.